Targeting of Cell Surface Proteolysis of Collagen XVII Impedes Squamous Cell Carcinoma Progression - Galiger, Célimène; Löffek, Stefanie; Stemmler, Marc; Kroeger, Jasmin K.; Mittapalli, Venugopal R.; Fauth, Lisa; Esser, Philipp R.; Kern, Johannes S.; Meiss, Frank; Laßmann, Silke; Bruckner-Tuderman, Leena; Franzke, Claus Werner (Molecular Therapy, 2017)
Squamous cell carcinoma (SCC) is one of the most common skin cancers and causes significant morbidity. Although the expression of the epithelial adhesion molecule collagen XVII (ColXVII) has been linked to SCC invasion, only little is known about its mechanistic contribution. Here, we demonstrate that ColXVII expression is essential for SCC cell proliferation and motility. Moreover, it revealed that particularly the post-translational modification of ColXVII by ectodomain shedding is the major driver of SCC progression, because ectodomain-selective immunostaining was mainly localized at the invasive front of human cutaneous SCCs, and exclusive expression of a non-sheddable ColXVII mutant in SCC-25 cells inhibits their matrix-independent growth and invasiveness. This cell surface proteolysis, which is strongly elevated during SCC invasion and metastasis, releases soluble ectodomains and membrane-anchored endodomains. Both released ColXVII domains play distinct roles in tumor progression: the endodomain induces proliferation and survival, whereas the ectodomain accelerates invasiveness. Furthermore, specific blockage of shedding by monoclonal ColXVII antibodies repressed matrix-independent growth and invasion of SCC cells in organotypic co-cultures. Thus, selective inhibition of ColXVII shedding may offer a promising therapeutic strategy to prevent SCC progression.
EVALuna2:10235